Fluorescence resonance energy transfer (FRET) as biomarkers. (2021) - Paul, Ripa; Suklabaidya, Sudip; Arshad Hussain, Syed
Abstract: Applications of Fluorescence Resonance Energy Transfer (FRET) in biology have expanded tremendously in the last 25 years. This technique has become a staple technique in many biological and biophysical fields. FRET based chemical sensors and biosensors can play an important role as biomarkers. Development of new and effective FRET based assay for biological application is an emerging area of research needing multidisciplinary approach from biologists, chemists and physicists. Here we have discussed the use of FRET technique as biomarker.